Lung adenocarcinoma concurrent with congenital pulmonary aplasia of the right upper lobe: A case report - Min, Bo; Wang, Chu-xu; Liu, Juan; Gong, Li; Wang, Cheng-xiang; Zuo, Xiao-hua (Frontiers in Oncology, 2022)
Lung adenocarcinoma, the most common subtype of lung cancer, has been always imposed serious threat to human health. Congenital pulmonary dysplasia (CPD) lacking typical clinical manifestations is a rare developmental anomaly. Pulmonary aplasia, the rarest subtype of CPD, may present with a variety of symptoms and is frequently associated with other abnormalities. This report describes an 81-year-old woman who presented with an irritant cough. Chest computed tomography (CT) and three-dimensional (3D) reconstruction revealed an irregular mass with a diameter of 5 cm in right lower lobe adjacent to the hilum. CT also indicated a rightward mediastinal shift and the complete absence of ipsilateral upper lobar tissue with bronchus ending in a terminal cecum, resulting in a diagnosis of pulmonary aplasia. The patient accepted lobectomy and lymph node dissection without complication, histopathologic examination combined HE staining with immunohistochemistry identified the tumor as adenocarcinoma. Three months after surgery, the patient was free of respiratory symptoms without chest pain. This report highlights the necessity of comprehensive evaluation for lung malignancy concurrent with CPD and the importance of identifying the diagnosis of pulmonary dysplasia.